2020
DOI: 10.3390/app10134679
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polyethylene Glycol Crosslinked β-CD Polymers for the Removal of Methylene Blue

Abstract: The environment is at the heart of global worldwide discussion. This study describes the synthesis of ecofriendly polymers by a crosslinking reaction between β-cyclodextrin as the monomer and polyethylene glycol diglycidyl ether (PEDGE) as well as ethylene diglycidyl ether (EDGE) as the crosslinking agents. The studied polymers were characterized by several techniques, such as SEM, FTIR, TGA-TDA and XRD. Their adsorption properties for methylene blue under various conditions of pH, contact time and ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 76 publications
0
5
0
1
Order By: Relevance
“…The thermogravimetric analysis and derivative thermogravimetric analysis study of poly(ethylene glycol) diglycidyl ether (PEGDE) with a molecular weight M w of 500 g mol –1 has been reported in the literature. 51 Figure 9 shows that the 5% weight loss temperature ( T d5 ) of PEG-epoxy is below 200 °C. It was found that the PEG-epoxy thermal decomposition started at about 125 °C and was completely degraded at about 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The thermogravimetric analysis and derivative thermogravimetric analysis study of poly(ethylene glycol) diglycidyl ether (PEGDE) with a molecular weight M w of 500 g mol –1 has been reported in the literature. 51 Figure 9 shows that the 5% weight loss temperature ( T d5 ) of PEG-epoxy is below 200 °C. It was found that the PEG-epoxy thermal decomposition started at about 125 °C and was completely degraded at about 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of A L PEI shows weak peaks in the 1170–1050 cm −1 range that correspond to C-C, C-O-C and C-O (in alcohols) stretching vibrations (associated with carbohydrate ring), and C-N stretching. After epichlorohydrin-activation (including PEGDE grafting), the spectrum of Cl-A L PEI shows a series of peaks at 1080 cm −1 (C-O and C-C stretching), 1055 cm −1 (C-N stretching), 1001 cm −1 (C-O-C stretching), 949 cm −1 (epoxide asymmetric stretching, [ 60 ]), and 827 cm −1 (CH 2 -Cl stretching). The relative intensities of these bands decrease after phosphorylation (P*-A L PEI), while the sharp peak at 827 cm −1 disappears: the grafting operates quantitatively on the pending CH 2 -Cl groups.…”
Section: Resultsmentioning
confidence: 99%
“…The olive waste activated with KOH (OR-KOH) exhibits the highest adsorption capacity. The bio-based adsorbent OR-KOH/PEG-SG demonstrated greater adsorption of the dye when compared to activated carbon obtained from banana stem [38], Silica-PEG intercalated clay hybrids [20], Fe 3 O 4 /biochar nanocomposite [39], chitosan/laterite/iron oxide-based bio-composite [40] and PEG-Crosslinked β-CD polymers [19].…”
Section: Comparison With Other Adsorbentsmentioning
confidence: 99%
“…In some cases, their use produces delayed pollution, representing an additional environmental threat [11,12]. Recently, many adsorbents have been reported by researchers in the context of dye removal from wastewaters, such as agricultural wastes [13][14][15], super-absorbent hydrogels [16], chitosan-based adsorbents [17], Ba/Co-PEG nanocomposites [18], PEG-Crosslinked biomass polymers [19], and silica-PEG intercalated clay hybrids [20]. Using agricultural waste as an eco-friendly precursor would provide a valid alternative, assuring a lower economic and polluting impact [21,22].…”
Section: Introductionmentioning
confidence: 99%